Makna Sesajen dalam Tradisi Sedekah Bumi Di Dusun Krajan, Desa Tunahan: Kajian Eksploratif Berdasarkan Konsep Pattidāna dalam Ajaran Buddhis Theravāda - Arisna Putra (Jurnal Budi Pekerti Agama Buddha, 2024)
Tradisi Sedekah Bumi in Dusun Krajan, Tunahan Village, is a cultural practice rich in symbolic and spiritual meanings. This study aims to uncover the symbolic meanings of offerings in this tradition and examine their relevance to the concept of pattidāna in Theravāda Buddhism. The research employs a qualitative method with an ethnographic approach, using participant observation, in-depth interviews, and documentation for data collection. The findings show that offerings carry complex symbolic meanings as a form of spiritual communication with ancestors and unseen beings. Elements such as flowers, coffee, incense, and takir reflect values of spirituality, ancestral reverence, and gratitude toward nature. This practice is aligned with the concept of pattidāna, which refers to merit transfer to ancestors as an expression of spiritual solidarity and communal identity. The study concludes that Sedekah Bumi embodies an integration of local and Buddhist values, making it a significant cultural practice to preserve amidst the challenges of modernity and contemporary spiritual crises